The aboriginal intervention in colonial discourse: challenging white control of cross-racial intersubjectivity - Cerce, Danica (Penerbit Universiti Kebangsaan Malaysia, 2018)
Written against the background of critical whiteness studies, the article deals with the poetry of Romaine Moreton and Alf Taylor, two contemporary Aboriginal voices who are not yet widely recognised, although their work is powerful and compelling. They both use their medium to explore various aspects of indigeneity and to intervene in the public dynamics of racial separation. In their attempt to instil agency for the postcolonial Indigenous subject, they challenge what Sara Suleri (2003) calls “the static lines of demarcation” between colonial power and disempowered culture – the assumptions about such binary oppositions as domination and subordination, centre and margin, self and other, upon which the logic of coloniality often stands. In convening a cross-racial public, the rhetoric of the two poets’ critique generates a discursive guilt in non-Indigenous readers and foregrounds the need for the intersubjectivity of race; that is, a zone of mutual respect and cooperation between Indigenous and non-Indigenous people.